Identification of disulfidptosis-related subtypes in gastric cancer and GAMT is a key gene during disulfidptosis - Wenxue Wu; Guoqiang Tao; Zhiqing Chen; Qi Zhou (Scientific Reports)
Abstract Recent studies have found that disulfidptosis occurs in cells under glucose starvation. The role of this programmed death method in gastric cancer remains to be explored. Cluster analysis based on disulfidptosis related genes to analyze the differential characteristics of disulfidptosis subtypes. We construct a prognostic risk model using 12 differentially expressed genes of disulfidptosis subtypes. We also analyzed the disulfidptosis subtypes at single-cell resolution. We found that cluster 1 has a poor prognosis and is characterized by a younger age. Inhibiting the expression of GAMT genes associated with disulfidptosis subtypes can significantly inhibit the proliferation of gastric cancer cells, which may be an important target for gastric cancer treatment. Cluster 2 patients are more sensitive to various chemotherapy drugs and immunotherapy. Mesenchymal cells, especially myCAF, endothelial cells, and smooth muscle cells, have strong disulfidptosis scores. In summary, our study provides new insights into the role of disulfidptosis in gastric cancer, and this may be used to guide the treatment of gastric cancer.